PONTIANAK COFFEE SHOP - Novan, Novan; Kalsum, Emilya; Lestari, Lestari (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Pontianak as the economic center in West Kalimantan has many coffee shops spread around the city, this shows that people's interest in coffee is increasing. however, there are still very few coffee shops in Pontianak that have processing facilities, selling coffee tools and products, and there is no educational platform to provide information about coffee. Therefore, design for a coffee shop that provides facilities that can accommodate these needs. Research method for Pontianak Coffee Shop includes the stages of observation, data collecting, identification, data analysis, planning, and design concept. The design of the Pontianak Coffee Shop building is made with 3 functions, namely a commercial function, a production function, and an educational function which has supporting facilities such as processing, workshops, and sales. The building concept adopts a tropical building form, and touch of nature to the interior and exterior of the building. The concepts are applied in structural is the use of square columns, while the environmental and utility architectural concepts are in the form of balancing the use of natural and artificial energy, and using maximum of natural ventilation systems. Design results are coffee shops building that provides not only coffee but also becomes an icon for the region in particular and Pontianak in general.